An improved and extended GPS-derived 3D velocity field of the glacial isostatic - Lidberg, Martin; Johansson, Jan; Scherneck, Hans-Georg; Davis, J.L. (Journal of Geodesy, 2007)
We present a new GPS-derived 3D velocity field for the Fennoscandia glacial isostatic adjustment (GIA) area. This new solution is based upon 3,000 days of continuous GPS observations obtained from the permanent networks in Fennoscandia. The period encompasses a prolongated phase of stable observation conditions after the northern autumn of 1996. Several significant improvements have led to smaller uncertainties and lower systematic errors in the new solutions compared to our previous results. The GPS satellite elevation cut-off angle was lowered to 10°, we fixed ambiguities to integers where possible, and only a few hardware changes occurred over the entire network. The GAMIT/GLOBK software package was used for the GPS analysis and reference frame realization. Our new results confirmed earlier findings of maximum discrepancies between GIA models and observations in northern Finland. The reason may be related to overestimated ice-sheet thickness and glaciation period in the north. In general, the new solutions are more coherent in the velocity field, as some of the perturbations are now avoided. We compared GPS-derived GIA rates with sea-level rates from tide-gauge observations, repeated precise leveling, and with GIA model computations, which showed consistency. © Springer-Verlag 2006.